Pseudomonas aeruginosa: Evolution of Antimicrobial Resistance and Implications for Therapy - McCarthy, Kate (Seminars in Respiratory and Critical Care Medicine, 2015)
Pseudomonas aeruginosa is a formidable pathogen in the infection arena. It is able to easily adapt to the environment which it inhabits and can also colonize and invade the human host to cause serious infections. In 2011, it was responsible for 7.1% of all health care–associated infection in the United States. The morbidity and mortality of both blood stream infections and ventilator-associated pneumonia are significant. On a global scale, we have seen the development of not only multidrug resistance but also extensive and pan drug resistance in this organism. This is often associated with limited clonal types of which we now have epidemiological evidence of spread. With this has come reduced antibiotic treatment options. Consideration of antibiotic infusions, combination therapy, and inhalational therapy has occurred in an attempt to gain the upper ground. Gram-negative resistance has appropriately been described as a global emergency.
Keywords: Pseudomonas aeruginosa; bacteremia; ventilator-associated pneumonia; epidemiology; resistance; antibiotic treatment